An Overview of Non-Isolated Hybrid Switched-Capacitor Step-Up DC–DC Converters - Julio C. Rosas-Caro; Jonathan C. Mayo-Maldonado; Jesus E. Valdez-Resendiz; Avelina Alejo-Reyes; Francisco Beltran-Carbajal; Oswaldo López-Santos (Applied Sciences, 2022)
The increasing interest in renewable energy sources has brought attention to large voltage-gain dc–dc converters; among the different available solutions to perform a large voltage-gain conversion, this article presents an overview of non-isolated dc–dc converter topologies that utilize switched-capacitor circuits, i.e., diode-capacitors voltage multipliers. The review includes combinations of a traditional power stage with a diode-capacitor-based voltage multiplier, such as the multilevel boost converter. This article starts by reviewing switched-capacitor (SC) circuits, different topologies, and different types of charge exchange; it provides a straightforward analysis to understand the discharging losses. It then covers the multilevel boost converter and other topologies recently introduced to the state-of-the-art. Special attention is put on SC circuits with resonant charge interchange that have recently been probed to achieve very good efficiency. An additional contribution of the article is new proof of the discharging losses in resonant switched-capacitor circuits focused on the initial and final stored energy in capacitors, and this proof explains the relatively large efficiency obtained with SC resonant converters.